Pelaksanaan Masuk Kaum Dalam Pernikahan Masyarakat Pekal Perspektif ‘URF (Studi di Desa Medan Jaya dan Pulai Payung Kecamatan Ipuh Kabupaten Mukomuko) - Rahman, Afandi; Fahima, Iim; Khoiri, Qolbi (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2024)
Abstract: This research aims to answer two main problems. First, what are the consequences if the marriage is carried out without going through the process of joining the tribe? Second, how is the implementation of gender entry in marriage for the Pekal Tribe community from the 'Urf perspective. Research results 1) The consequences that occur if a marriage is carried out without entering the clan are that the marriage cannot be carried out at home, cannot carry out traditional ceremonies, is not managed and attended by traditional leaders, is not recognized by the traditional community, can receive sanctions for dissolution, is ostracized from the traditional community and lacks support and restrictions on customary rights, including the right to be involved in community activities. 2) How is the implementation of gender entry from the Urf' perspective. If you look at the scope of its use, it is included in 'urf Al-khas, in terms of its object it is included in 'urf Al-Amali, and if you look at it in terms of its implementation and purpose, it is permissible for 'urf shahih as long as there is no public belief that leads to things that are prohibited by the 'urf shahih religion and it can become prohibited 'urf fasid if it is applied in society but is contrary to Islamic values.Keywords: Entering the Family, Marriage, “Urf. Abstrak : Penelitian ini bertujuan untuk menjawab dua permasalahan utama. Pertama, apa Saja Konsekuensi jika pernikahan dilaksanakan tanpa melalui proses masuk Kaum? Kedua, bagaimana pelaksanaan masuk kaum dalam pernikahan bagi masyarakat Suku Pekal Perspektif 'Urf. Hasil penelitian 1) Konsekuensi yang terjadi jika pernikahan dilaksanakan tanpa masuk kaum adalah pernikahan tersebut tidak bisa dilakukan di rumah, tidak dapat melakukan acara adat beradat, tidak diurus dan dihadiri oleh penghulu adat, tidak diakui oleh masyarakat adat, bisa mendapatkan sanksi pembubaran, dikucilkan dari masyarakat adat dan kurangnya dukungan dan pembatasan hak-hak adat, termasuk hak untuk terlibat dalam kegiatan masyarakat. 2) Bagaimana pelaksanaan masuk kaum dalam perspektif Urf’. Bila dilihat ruang lingkup penggunaanya, termasuk kedalam ‘urf Al-khas, bila dari segi objeknya termasuk ‘urf Al-Amali, dan bila dilihat segi pelaksanaan dan tujuannya adalah boleh ‘urf shahih selama tidak ada kepercayaan masyarakat yang mengarah kepada hal yang dilarang agama ‘urf shahih dan bisa menjadi dilaranag ‘urf fasid apabila diterapkan dalam masyarakat namun bertentangan dengan nilai-nilai Islam.Kata Kunci: Masuk Kaum,  Pernikahan, “Urf.